(untitled) (Central Asian Journal of Medical Sciences, 2016)
Objectives: Intra-aortic balloon pump (IABP) is the most widely-used form of mechanical hemodynamic support in patients with cardiogenic shock. However, usefulness of IABP in the high-risk patient population is conflicting. We examined whether the patient prognosis in Taiwan forthose treated with IABP has improved in recent years. Methods: We used Taiwan’s National Health Insurance Research Database to retrospectively review 3145 (2358 men, 75% of cases) cardiogenic shock patients who were treated with primary percutaneous coronary intervention (PCI) due to acute myocardial infarction (AMI) between 2000 and 2012. The primary outcome was all-cause mortality and secondary outcome was heart failure. Results: A total of 1417 patients who received IABP therapy and 1728 patients who did not receive non-IABP were selected in this study. During the follow-up period, the adjusted hazard ratio for overall mortality was 1.22 (Cl 95%: 1.10-1.35, p<0.0001) and for overall heart failure was 1.24 (Cl 95%: 1.08-1.41, p <0.001). Risk factors for all-cause mortality were previous heart failure, diabetes, chronic kidney disease and hypertension. Conclusion: In this nationwide, population-based, retrospective cohort study in Taiwan, we found that mortality rate and heart failure rate did not decline in cardiogenic shock patients who underwent primary PCI plus IABP therapy.